An approximation approach for the simulation of vapor-liquid phase change by the volume-of-fluid method. (March 2021) - Yan, Xiaohong; Chen, Guang
Highlights: A simulation approach of vapor-liquid phase change is proposed. Interfaces are approximated to be parallel to cartesian axes. Film boiling, bubble growth and condensation problems are simulated. Simulation results agree well with theoretical solutions. Abstract: An approximation approach for the implementation of the phase change model based on the volume-of-fluid method is proposed. In each interfacial cell, the interface normal direction is approximated to be parallel to one Cartesian axis line. The interface position is determined by the volume fraction value of the interfacial cell. The mass flux and heat flux at the interface are calculated in terms of temperature values of neighbor cells. The phase change model is easily coupled with ANSYS-Fluent by user defined functions. Film boiling on a flat plate, bubble growth in superheated liquid and bubble condensation in subcooled liquid are simulated. Simulation results of all three problems agree well with available analytical solutions and experimental data, which verify the accuracy of current approximation approach.